PENGARUH PROFESIONALISME, INDEPENDENSI AUDITOR DAN KOMPLEKSITAS AUDIT TERHADAP KUALITAS AUDIT DENGAN PENDIDIKAN DAN PELATIHAN AUDIT SEBAGAI VARIABEL MODERASI - Andi Wajdi; Rossje V Suryaputri (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2013)
The objective of this research is to empirically analyze the influence of professionalism, auditor's independency, and audit complexity toward audit quality. And to empirically analyze about the influence of professionalism, auditor's independency, and audit complexity toward audit quality which is moderated by education and audit training, particularly for auditors who work for Public Accounting Firm in East Jakarta. The populations in this research are several auditors who work for Public Accounting Firm in East Jakarta. The samples are collected with convenience sampling method and total of samples are about 72 respondents from 11 PAFs spread all across East Jakarta. The questionnaire method was used for collecting primary data. And double regression linear were used to analyze the data that has been collected. The result of this research shows that professionalism, auditor's independency, and also audit complexity have positive influences toward audit quality, significantly. Also, education and audit training have a signifkant role as moderated variables in relationships between influence of professionalism, auditor's independency, and audit complexity toward audit quality.